Promising Therapeutic Functions of Bone Marrow Mesenchymal Stem Cells Derived-Exosome in Asthma - Jia-Ying Yuan; Xiang-Yun Wang; Zhi-Ying Tong; Yu-Chao Dong; Jia-Yi Zhao; Yi Zhang; Yan Shang (Canadian Respiratory Journal, 2022)
Asthma is a chronic inflammatory disturbance of the airways in which many cells and cellular elements are involved. Wheezing, breathlessness, chest tightness, and coughing, especially at night or in the early morning, are typical symptoms of asthma. At present, inhaled corticosteroid (ICS) and long-acting β-agonists (LABAs) are standard treatments for regular management. Oral corticosteroids (OCSs) were recommended for controlling asthma exacerbation but only for a short-term treatment because of the side effects on organs. Biologic therapies have achieved exciting and notable effects in clinical treatment but are not applicable for all phenotypes of asthma. At present, some new approaches are under exploration to lessen side effects and improve curative effects. Studies have revealed that bone marrow mesenchymal stem cells (BMMSCs) hold various curative effects in asthma and may benefit in the long term with high safety. Extracellular vesicles (EVs) enriched in body fluid were characterized as subcomponents of extracellular vesicles and delivered carriers combined with genetic messages in vivo. The therapeutic potential of exosomes has become a research hotspot in many diseases. BMMSC-derived exosomes were considered as the dominant part of BMMSCs in cell-to-cell communications and playing curative effects. Points also hold that BMMSC-Exo could interfere with airway inflammation and airway remolding in asthma via modulating the immune response, regulating gene expression, adjusting the phenotype of macrophage, etc. However, BMMSC-Exo still lacked more clinical trials for evaluating the effects on asthma, and the technology of extraction and purification still needs to be improved for wide use. This review aims to draw the relationship among asthma, BMMSC, and exosome, which may provide innovate ideas for treatment of asthma, and arouse attention about the curative potential of BMMSC-Exo.